Desenvolvimento de métodos analíticos para monitoramento multirresidual de agrotóxicos em amostras de solo e água da sub-bacia hidrográfica do Ribeirão Santa Maria/GO - Goulart, Adilson Correia (2024)
Pesticide residues are among the leading environmental contaminants in the world, contaminating soils, water resources, and non-target organisms. They monitored studies of pesticide residues in places where agricultural practices occur intensively and have become necessary in several regions of Brazil. Thus, the objective of this study was to develop and validate two analytical methods for the determination of residues of carbendazim, thiodicarb, diuron, fipronil, and chlorpyrifos in soil and surface water samples from the Ribeirão Santa Maria sub-basin/GO. Solid-liquid extraction and liquid-liquid extraction with low-temperature partitioning were selected as sample preparation techniques for extracting pesticide residues from the samples, as well as high-performance liquid chromatography with UV detection to analyze the extracts. The sample preparation techniques were initially optimized regarding the volume of acetonitrile, vortexing time, addition of NaCl, and freezing time in the recovery of pesticides from soil and water samples. The optimized conditions were 6.0 mL of acetonitrile, 1.0 min of vortexing, no addition of NaCl to the samples, and a freezing time of 4.0 h, resulting in recoveries between 85-110% and relative standard deviations <13% for both samples. The methods were then validated for selectivity, linearity, working range, matrix effect, limits of detection and quantification, accuracy, precision, and robustness, following the validation guide proposed by the European Community in document SANTE/11312/2021. The validated methods for determining the five pesticides in soil and water samples showed recovery rates within the range of 80 to 120% and relative standard deviations <20%, in addition to being robust as measured by the Youden test. The methods also presented 78 points in the eco-scale metric, characterizing them as green methods with low environmental impact. The methods for determining the pesticides carbendazim, thiodicarb, diuron, fipronil, and chlorpyrifos were applied to soil and surface water samples from the Ribeirão Santa Maria sub-basin/GO collected between July/2023 and March/2024. The results of the analyses did not indicate the presence of pesticides in the soil samples' extracts. However, in the study of extracts from surface water samples, peaks were detected in the retention times of the pesticides carbendazim and thiodicarb, reinforcing the importance of monitoring pesticide residues in areas of intense agricultural activity and the applicability of the methods proposed in this work.